2022
DOI: 10.3390/antiox11061134
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Anthocyanin Concentrations, Total Metabolite Contents and Antioxidant Activities in Adzuki Bean Cultivars

Abstract: In this study, adzuki bean cultivars including Arari, Chilbopat, Geomguseul, and Hongeon were recently cultivated, and the concentrations of seven individual anthocyanins were determined in their seed coats for the first time. Moreover, the variations of total saponin content (TSC), total phenolic content (TPC), 1,1-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, Trolox equivalent antioxidant capacity (TEAC), and ferric reducing antioxidant power (FRAP) between defatted and undefatted extracts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…This causes the breakdown of the sugar-phosphate backbone resulting in strand breaks [ 41 ]. Many previous studies reported that natural extracts with strong antioxidant properties showed high potential to prevent and repair oxidative DNA damage caused by reactive oxygen species (ROS) in living cells [ 35 , 42 , 43 ]. Antioxidants, including phenolics, flavonoids, carotenoids, and terpenoids, have been observed to interact with ROS, generating inert compounds that mitigate oxidative damage [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This causes the breakdown of the sugar-phosphate backbone resulting in strand breaks [ 41 ]. Many previous studies reported that natural extracts with strong antioxidant properties showed high potential to prevent and repair oxidative DNA damage caused by reactive oxygen species (ROS) in living cells [ 35 , 42 , 43 ]. Antioxidants, including phenolics, flavonoids, carotenoids, and terpenoids, have been observed to interact with ROS, generating inert compounds that mitigate oxidative damage [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity may also be facilitated by saponins. There is a correlation between saponins and antioxidant activity, including the scavenging activity on DPPH free radicals [20].…”
Section: Antiamylase Activitymentioning
confidence: 99%
“…Total metabolites, the saponin and phenolics contents, ranged from 16 to 945 mg DE g -1 and 0.80-57.35 mg GAE g -1 , respectively. Delphinidin-3-O-glucoside and delphinidin-3-O-galactoside were the predominant anthocyanins in black-seeded adzuki bean cultivars (Desta et al, 2022). Seed coat is a rich source of metabolites and closely associated with the anthocyanin and flavonoid metabolism pathways.…”
Section: Seed Nutritional Diversitymentioning
confidence: 99%